Integrasi Religius Moderasi dan Ketahanan Nasional Dalam Mengatasi Aksi Terorisme Berbasis Politik Islam di Indonesia - Fauzi Rusli (CV. Rayyan Dwi Bharata, 2025)
This study examines the integration of the values of religious moderation and the concept of national resilience in addressing the challenges of political Islamic extremism faced by Indonesia. The phenomenon of political Islamic extremism has become a critical issue in various parts of the world, including Indonesia, which faces threats to its social, political, and national security. The concept of religious moderation in Islam is analyzed as a foundation for accepting change, promoting renewal, peace, unity, and justice. Meanwhile, the concept of national resilience includes archipelagic insights, national awareness, the cultivation of national values, religious moderation, and cross-cultural dialogue. The integration of these two concepts provides a strong basis for countering extremist ideologies by promoting deep understanding, tolerance, unity, and cooperation within society. This research holds significant implications in efforts to build a harmonious society and maintain national stability against the negative impacts of political Islamic extremism.